Analisis Penerapan Kurikulum di SDS Katolik Santo Arnoldus Janssen Kecamatan Bulik Kabupaten Lamandau - DEWI ASTUTI, SRIYANTI; DEBORA; NYOTO (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2024)
This research aims to analyze the implementation of the 2013 Curriculum in teaching at the Private Catholic Elementary School Santo Arnoldus Janssen, Bulik Subdistrict, Lamandau Regency. The 2013 Curriculum is a national curriculum that emphasizes the formation of competencies and character of learners. Despite its commendable objectives, there are several challenges in its implementation, such as incomplete teacher understanding and students' difficulties in comprehending thematic materials. This research employs a qualitative approach with data collection techniques including observation and structured interviews. The research takes place at SDS Catholic Santo Arnoldus Janssen. Observations indicate that teachers have been able to prepare and manage learning effectively, using engaging teaching strategies and encouraging active student participation. Furthermore, students exhibit good activity levels in following the learning process, both physically, mentally, and emotionally. The impact of implementing the 2013 Curriculum is evident in the quality of students who are competent, productive, creative, and independent. Effective and efficient learning resources have been utilized well by teachers, despite limitations in the use of laptops. Learning also stimulates the holistic growth of affective, cognitive, and psychomotor aspects in students. A safe, comfortable, and orderly learning environment is created through consistent rule enforcement and active student participation. Additionally, continuous evaluation and improvement processes are implemented.